2017
DOI: 10.1002/jcop.21885
|View full text |Cite
|
Sign up to set email alerts
|

Impact of victimization, community climate, and community size on the mental health of sexual and gender minority youth

Abstract: Sexual and gender minority (SGM) youth are at risk of stigma and victimization, which may lead to increased mental health symptoms, including depression, anxiety, and stress. The role of the community in exacerbating or mitigating the frequency of victimization and mental health symptoms among SGM youth has been understudied. Using a minority stress framework, this study examined the association between physical and nonphysical anti‐SGM victimization, perceived community climate, and community size and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 49 publications
(95 reference statements)
2
23
0
6
Order By: Relevance
“…We found that in large cities, children in LG-parent families experienced less victimization than children in heterosexualparent families, according to parent reports, whereas in more rural regions, children with LG parents experienced more victimization than children with heterosexual parents (albeit non-significantly so). This finding dovetails with work on LGBTQ youth which documented greater victimization among youth living in rural communities (Kosciw et al, 2009) and youth living in self-described hostile and small towns (Paceley et al, 2017). The current study-which included both parents' reports, used a comparison sample of heterosexual parents, and looked at victimization more broadly-also builds on and echoes Power et al (2014) study of Australian LGBTQ parents, which found that parents living in less urban areas were more likely to report that their children experienced homophobic bullying or discrimination at school.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that in large cities, children in LG-parent families experienced less victimization than children in heterosexualparent families, according to parent reports, whereas in more rural regions, children with LG parents experienced more victimization than children with heterosexual parents (albeit non-significantly so). This finding dovetails with work on LGBTQ youth which documented greater victimization among youth living in rural communities (Kosciw et al, 2009) and youth living in self-described hostile and small towns (Paceley et al, 2017). The current study-which included both parents' reports, used a comparison sample of heterosexual parents, and looked at victimization more broadly-also builds on and echoes Power et al (2014) study of Australian LGBTQ parents, which found that parents living in less urban areas were more likely to report that their children experienced homophobic bullying or discrimination at school.…”
Section: Discussionsupporting
confidence: 74%
“…Research on LGBTQ youth has found similar associations. A study of LGBTQ youth ages 14-18 documented greater levels of victimization among participants living in what they perceived as hostile and small towns (Paceley et al, 2017). And, research on LGBTQ youth (mean age = 15.9 years) found that youth living in rural communities reported higher levels of victimization (Kosciw et al, 2009).…”
Section: Community Factors As Predictors Of Victimizationmentioning
confidence: 99%
“…This study draws important conclusions about the relationship between victimization and health among nonmetropolitan SMY; however, it did not examine the relationship between community and health. One prior work using data from the current study examined the collective impact of victimization, community size, and climate on mental health outcomes among SGM youth and found that only nonphysical victimization predicted increases in depression, anxiety, and stress, whereas community size predicted increases in stress only (Paceley et al, 2017a). Community climate was not significant in these findings.…”
Section: Mstmentioning
confidence: 83%
“…A few studies have documented the relationship between SGM identity, victimization, and health outcomes. Nonphysical victimization, such as overhearing anti-SGM comments or being teased, is associated with increased depression, anxiety (Paceley, Goffnett, & Gandy-Guedes, 2017a; Tucker et al, 2016), and stress (Woodford, Paceley, Kulick, & Hong, 2015) among SGM youth. Perceived discrimination mediates the relationship between sexual orientation and symptoms of depression (Almeida et al, 2009), heavy alcohol use (Fish et al, 2019; Pollitt, Mallory, & Fish, 2018), and self-reported physical health (Mereish & Poteat, 2015).…”
Section: Mstmentioning
confidence: 99%
“…Stigma may manifest as external and internal processes and occur across socioecological levels, including individual (e.g., internalization of negative stereotypes among the minority group; experiences of microaggressions and discrimination), community (e.g., community climate, perceptions of sexual prejudice), and structural levels (e.g., public policies, cultural norms, cultural ideologies; Grossman & Stangl, ; Link & Phelan, ; Paceley, Goffnett, & Gandy‐Guedes, ). Earnshaw and Chaudoir's () conceptual framework, illustrating how HIV‐related stigma influences HIV‐related health outcomes, is a useful framework for understanding the relationships between mechanisms of stigma (e.g., perceived community prejudice, IH, enacted stigma) and HIV‐related outcomes.…”
Section: Introductionmentioning
confidence: 99%